Training the next generation of disaster risk managers through sustainability research and teaching (2016)
Disaster risk management is an integral part of sustainability, and curricula that are focused on sustainability can be broadened to include disaster risk management. The David O’Brien Centre for Sustainable Enterprise at Concordia University researches and teaches disaster risk management through involvement in a collaborative project with the United Nations’ Future Earth network to develop a Sustainable Financial and Economic System Knowledge-to-Action Network (SFES-KAN). The definition of ‘sustainable’ in this context includes disaster risk management. The SFES-KAN aims to align the current financial system with the UN’s sustainable development goals by identifying research gaps and facilitating interdisciplinary research between academics, practitioners, and policymakers to fill those gaps. Our research on such topics as risk management and sustainable investing for the SFES-KAN project has translated into research on disaster risk management and has led to curriculum development on these topics. The goal of our paper is to provide other institutions with examples and strategic information on how to translate such interdisciplinary and solution-oriented sustainability research into research and curricula on disaster risk management.